Awareness level on mental illness among secondary school students in Skudai, Johor - Nik Mustafa, Nik Murni (Science Publishing Group, 2015)
Adolescents diagnosed with mental illness in Malaysia have increased these past few years despite various health campaigns and awareness programs organised by the government and private sectors. Thus, this research aims to investigate the students’ awareness level and perception on mental illness. Questionnaires have been distributed to 118 form four secondary school students in Skudai, Johor. Findings from the study show that most of the respondents are fairly ignorant of mental illness and they revealed that the promotion of mental health and wellness is still lacking in Malaysia. They also believed that mental illness is still being surrounded with stigma and discrimination over the years. Nonetheless, the respondents have relatively positive views on mental health patients and the illness itself.